Sulfonated cellulose, preparation method thereof and application of sulfonated cellulose as filtrate reducer for drilling fluid
By introducing sulfonic acid groups on the cellulose molecular chain to prepare sulfonated cellulose, the problem of failure of existing treatment agents in high temperature and high calcium salt environments is solved, and wider applicability and higher performance stability are achieved.
Patent Information
- Application Number
- CN202311198882.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
AI Technical Summary
The existing cellulose drilling fluid treatment agent fails in high temperature and high calcium salt environments, and cannot meet the drilling needs of complex formations.
By introducing sulfonate groups on the cellulose molecular chain, sulfonated cellulose is prepared and its sulfonation degree is increased by the etherification reaction of water-soluble halosulfonate.
It improves the temperature resistance, high-valent metal ions and calcium resistance of drilling fluid, expands the scope of application, and enhances thermal stability.
Smart Images

Figure BDA0004453363390000091 
Figure BDA0004453363390000101 
Figure HDA0004453363470000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of drilling fluid, and in particular relates to sulfonated cellulose, a preparation method thereof and application thereof as a fluid loss reducer for drilling fluid. Background Art
[0002] Cellulose is the most widely distributed and abundant polysaccharide in nature. Water-soluble cellulose ether derivatives are one of the earliest, most widely used and most widely used green and environmentally friendly drilling fluid treatment agents in modified natural material oilfield chemicals. Commonly used cellulose treatment agents in drilling are mainly carboxymethyl (ethyl) cellulose (CMC) and polyanionic cellulose (PAC), which have the application effects of reducing filtration loss, improving mud cake quality, adjusting drilling fluid rheology, and improving suspension stability in drilling fluid. However, since the carboxylic acid group in the molecular structure is sensitive to high-valent metal ions, precipitation is formed when encountering calcium and magnesium ions, resulting in the ineffectiveness of the treatment agent, which cannot meet the drilling needs of calcium chloride drilling fluid and complex formations such as high calcium salt and high temperature, seriously affecting the scope of application. Improving the temperature resistance and high-valent salt resistance of modified cellulose products is of great significance for improving the performance of treatment agents, controlling costs, and promoting the greening of drilling fluids.
[0003] The introduction of sulfonic acid groups into natural products can develop drilling fluid treatment agents with excellent resistance to temperature, salt, and especially calcium ion pollution, and the sulfonic acid groups in the products are also conducive to improving the thermal stability of drilling fluids and expanding the scope of application. The Chinese patent with publication number CN108101999A discloses a sulfoalkylated starch, its preparation method and application. By introducing sulfonic acid groups into starch, when the sample is added with 1.5wt%, the medium pressure filtration loss in saturated brine drilling fluid with CaCl2 pollution added in the range of 0wt% to 10wt% at room temperature is less than 15ml, and the calcium resistance is significantly better than that of carboxymethyl starch (CMS). The Chinese patent with publication number CN115926761A discloses a method for preparing a modified cellulose fluid loss reducer, which introduces carboxyl and sulfonic acid groups into wood pulp powder cellulose by adding chloroacetic acid and chlorohydroxysulfonate, so that the modified cellulose fluid loss reducer still has good hydration ability under high temperature and high salt, and improves the salt resistance and temperature resistance of the modified cellulose fluid loss reducer. Since the sulfonic acid group also has excellent calcium resistance, the patent does not mention the sulfonation degree and calcium resistance of the product, and the sulfonating agent chlorohydroxysulfonate used in the method has a large steric hindrance, and it is difficult to ensure the amount of sulfonic acid group introduced.
[0004] Sulfonation modification of cellulose is the introduction of sulfonic acid groups into the cellulose molecular chain. The corresponding reaction process of introducing sulfonic acid groups into the molecule is called sulfonation reaction. According to the different reaction mechanisms, it can be divided into direct sulfonation method and oxidative sulfonation method.
[0005] Direct sulfonation is a method of introducing sulfonic acid groups into the hydroxyl positions of cellulose molecular chains using sulfonating agents such as concentrated sulfuric acid, fuming sulfuric acid, sulfur trioxide, chlorosulfonic acid, sulfur dioxide plus oxygen and sodium sulfite. Figure 1 As shown. The sulfonation reaction is relatively complicated, and it needs to undergo a process of absorbing heat first, then releasing a large amount of heat, and then reacting smoothly. Each controlled temperature during the reaction has a great influence on the quality and performance of the final product. The Chinese patent with publication number CN109279808A discloses a sulfonated cellulose water reducer based on a porous carbon sulfonic acid catalyst loaded with elemental tin and a preparation method thereof. The sulfonating agent is a mixture of sulfur trioxide and air. The porous carbon sulfonic acid prepared by the sulfonation reaction of the porous carbon material is used as a carrier, and elemental tin is deposited on the surface, which not only improves the catalytic activity of the catalyst, but also makes the catalyst have a certain phase change and sulfonation effect, which is conducive to maintaining the stability of the temperature of the cellulose sulfonic acid process, and works in conjunction with an intermittent reactor to increase the sulfonation rate of the sulfonated cellulose, thereby improving the performance of the water reducer. However, the use of concentrated sulfuric acid, chlorosulfonic acid, and sulfur trioxide alone in the direct sulfonation method will cause a large amount of polysaccharide degradation. Improved methods in Lewis base media, such as sulfur trioxide-pyridine method, chlorosulfonic acid-formamide method, chlorosulfonic acid-pyridine method, etc., can greatly reduce degradation, but cannot avoid esterification reactions and will produce a large amount of waste liquid.
[0006] The oxidative sulfonation method uses an oxidant to oxidize cellulose into aldehyde cellulose, and then uses sodium bisulfite as a sulfonating agent to sulfonate the product, such as Figure 2 As shown. The Chinese patent with publication number CN1126260 discloses sulfonated cellulose and its preparation method, wherein cellulose fibers are oxidized with oxidants such as sodium metaperiodate / sodium paraperiodate / periodic acid / sodium hypochlorite to form aldehyde cellulose, the cellulose fibers are washed with water, and then sodium bisulfite is used as a sulfonating agent to sulfonate the oxidized cellulose at about 25°C to 90°C and pH 3 to 4.5 to form sulfonated cellulose with a sulfonate substitution degree of about 0.01 to 0.1. The Chinese patent with publication number CN111363524A discloses a high temperature and salt resistance anti-slump filter loss agent for drilling fluid, which uses 30°C to 60°C oxidation to form aldehyde groups on the cellulose molecular chain, and sulfonates with chlorosulfonic acid solution to prepare a high temperature and salt resistance anti-slump filter loss agent for drilling fluid, which solves the problem of reduced performance of sodium carboxymethyl cellulose filter loss agent at high temperature, making it have the advantages of high temperature resistance and salt resistance. Similarly, Chinese patent publication number CN112142862A discloses a method for preparing sulfonated cellulose, wherein dialdehyde cellulose is first obtained in an ethanol medium, and then sulfonated with at least one sulfonating agent selected from bisulfite, pyrosulfite and pyrosulfite. However, the oxidative sulfonation method requires the use of an oxidant to oxidize cellulose into aldehyde cellulose, and it is difficult to avoid the destruction of the main structure of cellulose. Summary of the invention
[0007] In view of this, the technical problem to be solved by the present invention is to provide a sulfonated cellulose with strong resistance to temperature and calcium, a preparation method thereof and an application thereof as a fluid loss reducer for drilling fluid.
[0008] The invention provides a sulfonated cellulose obtained by etherifying alkalized cellulose with water-soluble halogenated sulfonate.
[0009] Preferably, the water-soluble halogenated sulfonate is a halogenated alkyl sulfonate.
[0010] Preferably, the water-soluble halosulfonate is selected from sodium 2-chloroethanesulfonate and / or sodium 2-bromoethanesulfonate.
[0011] Preferably, the sulfonation degree of the sulfonated cellulose is 0.4 to 1.0.
[0012] Preferably, the method comprises the following steps:
[0013] In a protective atmosphere, alkalized cellulose and water-soluble halogenated sulfonate are heated under the action of a catalyst to carry out an etherification reaction to obtain sulfonated cellulose.
[0014] Preferably, the alkalized cellulose is prepared according to the following steps:
[0015] In a protective atmosphere, cellulose is dispersed in an alcohol solvent, and a sodium hydroxide aqueous solution is added to carry out an alkalization reaction to obtain alkalized cellulose.
[0016] Preferably, the mass concentration of the sodium hydroxide aqueous solution is 25% to 60%; and the molar ratio of the cellulose to the sodium hydroxide in the sodium hydroxide aqueous solution is 1:1 to 1:4.
[0017] Preferably, the catalyst is selected from quaternary ammonium salt catalysts; the molar ratio of the catalyst to the water-soluble halogenated sulfonate is 0.05:1 to 2:1;
[0018] The molar ratio of the water-soluble halogenated sulfonate to the cellulose is 0.5:1 to 2:1.
[0019] Preferably, the temperature of the alkalization reaction is 10°C to 40°C; the time of the alkalization reaction is 0.5 to 2 hours; the temperature of the etherification reaction is 60°C to 80°C; the time of the etherification reaction is 3 to 7 hours.
[0020] The present invention also provides an application of the sulfonated cellulose as a fluid loss reducer for drilling fluid.
[0021] The present invention provides a sulfonated cellulose, which is obtained by etherifying alkalized cellulose with a water-soluble halogenated sulfonate. Compared with the prior art, the sulfonated cellulose provided by the present invention contains sulfonic acid groups and hydroxyl groups, and can be used in drilling fluids to effectively control the filtration loss of drilling fluids while improving the resistance of drilling fluids to salt pollution, especially the resistance to calcium ion pollution; and the sulfonic acid groups in the product are also conducive to improving the thermal stability of drilling fluids and expanding the scope of application. In short, compared with carboxymethyl cellulose used in drilling fluids, the sulfonated cellulose provided by the present invention has obvious resistance to temperature and high-valent metal ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The mechanism diagram of direct sulfonation method;
[0023] Figure 2 The diagram is the mechanism of the oxidative sulfonation method;
[0024] Figure 3 The infrared spectra of the raw material cellulose and the obtained sulfonated cellulose used in Example 6 of the present invention;
[0025] Figure 4 This is a comparison chart of the fresh water slurry performance of Example 5 of the present invention and the comparative example;
[0026] Figure 5 This is a performance comparison diagram of 4% salt water slurry of Example 5 of the present invention and the comparative example;
[0027] Figure 6 This is a performance comparison diagram of saturated salt water slurry of Example 5 of the present invention and the comparative example;
[0028] Figure 7 The performance comparison diagram of Example 5 of the present invention and the comparative example in 3% calcium chloride slurry is shown. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] The invention provides a sulfonated cellulose obtained by etherifying alkalized cellulose with water-soluble halogenated sulfonate.
[0031] The alkalized cellulose may be any alkalized cellulose known to those skilled in the art without any particular limitation. In the present invention, the cellulose is preferably alkalized with a sodium hydroxide aqueous solution.
[0032] The water-soluble halogenated sulfonate is preferably a halogenated alkyl sulfonate, more preferably sodium 2-chloroethanesulfonate and / or sodium 2-bromoethanesulfonate.
[0033] The sulfonation degree of the sulfonated cellulose is preferably 0.4-1, more preferably 0.41-0.9, and even more preferably 0.41-0.82; in the embodiments provided by the present invention, the sulfonation degree of the sulfonated cellulose is specifically 0.45, 0.82, 0.6, 0.51, 0.74 or 0.41.
[0034] The sulfonated cellulose provided by the present invention contains sulfonic acid groups and hydroxyl groups, etc., and can be used in drilling fluid to effectively control the filtration loss of drilling fluid and improve the resistance of drilling fluid to salt pollution, especially the resistance to calcium ion pollution; and the sulfonic acid groups in the product are also beneficial to improving the thermal stability of drilling fluid and expanding the scope of application. In short, compared with carboxymethyl cellulose used in drilling fluid, the sulfonated cellulose provided by the present invention has obvious resistance to temperature and high-valent metal ions.
[0035] The present invention also provides a method for preparing sulfonated cellulose, comprising the following steps: in a protective atmosphere, heating alkalized cellulose and water-soluble halogenated sulfonate under the action of a catalyst to carry out an etherification reaction to obtain sulfonated cellulose.
[0036] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.
[0037] According to the present invention, the alkalized cellulose is prepared according to the following steps: in a protective atmosphere, cellulose is dispersed in an alcohol solvent, and a sodium hydroxide aqueous solution is added for alkalization reaction to obtain the alkalized cellulose; the protective atmosphere can be a protective atmosphere well known to those skilled in the art, and there is no special restriction. In the present invention, nitrogen is preferably used; the alcohol solvent is preferably one or more of ethanol, isopropanol and ethylene glycol; the ratio of cellulose to alcohol solvent is preferably 10g: (100-300)mL, more preferably 10g: (100-200)mL, and more preferably 10g: (130-200)mL; the volume ratio of alcohol solvent to water in the alkalization reaction system is preferably 5:5-9:1, more preferably 6:4-9:1, and more preferably 7:3-9:1; the mass concentration of the sodium hydroxide aqueous solution is preferably The content of cellulose in the aqueous solution of sodium hydroxide is preferably 25% to 60%, more preferably 30% to 50%; in the embodiment provided by the present invention, the mass concentration of the aqueous solution of sodium hydroxide is specifically 30%, 40% or 50%; the molar ratio of the cellulose to the sodium hydroxide in the aqueous solution of sodium hydroxide is preferably 1:1 to 1:4; in the embodiment provided by the present invention, the molar ratio of the cellulose to the sodium hydroxide in the aqueous solution of sodium hydroxide is specifically 1:1, 1:2, 1:3 or 1:4; the temperature of the alkalization reaction is preferably 10°C to 40°C, more preferably 15°C to 40°C; in the embodiment provided by the present invention, the temperature of the alkalization reaction is specifically 15°C, 20°C or 40°C; the time of the alkalization reaction is preferably 0.5 to 2h; in the embodiment provided by the present invention, the time of the alkalization reaction is specifically 0.5h, 1h or 2h.
[0038] In a protective atmosphere, alkalized cellulose and a water-soluble halogenated sulfonate are heated under the action of a catalyst to carry out an etherification reaction; the types of the water-soluble halogenated sulfonate are the same as those described above and are not repeated here; the molar ratio of the water-soluble halogenated sulfonate to cellulose is preferably 0.5:1 to 2:1; in the embodiments provided by the present invention, the molar ratio of the water-soluble halogenated sulfonate to cellulose is specifically 0.5:1, 1:1, 1.5:1 or 2:1; the catalyst is preferably a quaternary ammonium salt catalyst, more preferably one or more of tetrabutylammonium bromide, benzyltriethylammonium chloride, tetrabutylammonium chloride, dodecyltrimethylammonium chloride and tetradecyltrimethylammonium chloride; the molar ratio of the catalyst to the water-soluble halogenated sulfonate is It is preferably 0.05:1-2:1, more preferably 0.05:1-1:1, further preferably 0.05-0.5:1, and most preferably 0.05:1-0.2:1; in the embodiment provided by the present invention, the molar ratio of the catalyst to the water-soluble halogenated sulfonate is specifically 0.05:1, 0.1:1, 0.2:1 or 0.15:1; the temperature of the etherification reaction is preferably 60°C-80°C, more preferably 65°C-80°C; in the embodiment provided by the present invention, the temperature of the etherification reaction is specifically 65°C, 70°C or 80°C; the time of the etherification reaction is preferably 3-7h; in the embodiment provided by the present invention, the time of the etherification reaction is specifically 3h, 4h or 7h.
[0039] After the etherification reaction is completed, an acid solution is preferably added to adjust the pH to 7-9, and after centrifugation, sulfonated cellulose is obtained; the acid solution can be an acid solution well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably one or more of hydrochloric acid solution, acetic acid solution and sulfuric acid solution; the amount of acid solution added is preferably adjusted to adjust the pH value of the reaction solution to 7-8.5; after centrifugation, it is preferably washed with an alcohol aqueous solution, centrifuged, and dried to obtain sulfonated cellulose.
[0040] The preparation method provided by the invention has simple process, low production cost, high production efficiency, stable product quality and is conducive to application.
[0041] The present invention also provides an application of the sulfonated cellulose as a fluid loss reducer for drilling fluid.
[0042] The present invention also provides a drilling fluid, comprising the above-mentioned sulfonated cellulose.
[0043] In order to further illustrate the present invention, the following is a detailed description of the present invention providing a sulfonated cellulose, a preparation method thereof and an application thereof as a fluid loss reducer for drilling fluid in combination with embodiments.
[0044] The reagents used in the following examples are all commercially available.
[0045] Example 1
[0046] Under stirring and nitrogen protection conditions, according to the molar ratio of cellulose: sodium hydroxide: sodium 2-bromoethanesulfonate: tetrabutylammonium bromide = 1:1:0.5:0.025, the volume ratio of alcohol to water is 7:3, 10g of cellulose is added to 130mL of ethanol solvent, and then a sodium hydroxide solution with a mass fraction of 30% is added, and the reaction is alkalized in a 15°C water bath for 0.5h; sodium 2-bromoethanesulfonate and tetrabutylammonium bromide in a formula amount are added, the temperature is raised to 65°C, and the reaction is maintained for 3h to obtain a reaction solution; the reaction is neutralized with a hydrochloric acid solution to a pH value of 7-8.5, and then the reactant is centrifuged to separate the organic solvent, and then it is repeatedly washed and centrifuged with an ethanol solution, and finally placed in a vacuum drying oven for drying to obtain a sulfonated cellulose product, and the number average molecular weight of the obtained product is M n 2.01×10 5 .
[0047] Example 2
[0048] Under stirring and nitrogen protection conditions, according to the molar ratio of cellulose: sodium hydroxide: sodium 2-chloroethanesulfonate: tetrabutylammonium bromide = 1:2:1.0:0.1, the volume ratio of alcohol to water is 7:3, 10g of cellulose is added to 150mL of ethanol solvent, and then a sodium hydroxide solution with a mass fraction of 40% is added, and the reaction is alkalized in a water bath at 15°C for 0.5h; sodium 2-bromoethanesulfonate and tetrabutylammonium bromide in the formula amount are added, the temperature is raised to 65°C, and the reaction is maintained for 3h to obtain a reaction solution; the reaction is neutralized with a hydrochloric acid solution to a pH value of 7-8.5, and then the reactant is centrifuged to separate the organic solvent, and then it is repeatedly washed and centrifuged with an ethanol solution, and finally placed in a vacuum drying oven for drying to obtain a sulfonated cellulose product, and the number average molecular weight of the obtained product is M n 2.51×10 5 .
[0049] Example 3
[0050] Under stirring and nitrogen protection conditions, according to the molar ratio of cellulose: sodium hydroxide: sodium 2-chloroethanesulfonate: benzyltriethylammonium chloride = 1:4:1.5:0.3, the volume ratio of alcohol to water is 8:2, 10g of cellulose is added to 150mL of ethanol solvent, and then a sodium hydroxide solution with a mass fraction of 40% is added, and the reaction is alkalized in a 20°C water bath for 0.5h; sodium 2-bromoethanesulfonate and tetrabutylammonium bromide are added in a formula amount, the temperature is raised to 70°C, and the reaction is maintained for 3h to obtain a reaction solution; the reaction is neutralized with a hydrochloric acid solution to a pH value of 7-8.5, and then the reactant is centrifuged to separate the organic solvent, and then it is repeatedly washed and centrifuged with an ethanol solution, and finally placed in a vacuum drying oven for drying to obtain a sulfonated cellulose product, and the number average molecular weight of the obtained product is M n 2.42×10 5 .
[0051] Example 4
[0052] Under stirring and nitrogen protection conditions, according to the molar ratio of cellulose: sodium hydroxide: sodium 2-chloroethanesulfonate: benzyltriethylammonium chloride = 1:4:1.5:0.3, the volume ratio of alcohol to water is 8:2, 10g of cellulose is added to 150mL of ethanol solvent, and then a sodium hydroxide solution with a mass fraction of 40% is added, and the reaction is alkalized in a 40°C water bath for 1.0h; sodium 2-chloroethanesulfonate and benzyltriethylammonium chloride in the formula amount are added, the temperature is raised to 70°C, and the reaction is maintained for 4h to obtain a reaction solution; the reaction is neutralized with a hydrochloric acid solution to a pH value of 7-8.5, and then the reactant is centrifuged to separate the organic solvent, and then it is repeatedly washed and centrifuged with an ethanol solution, and finally placed in a vacuum drying oven for drying to obtain a sulfonated cellulose product, and the number average molecular weight of the obtained product is M n 2.48×10 5 .
[0053] Example 5
[0054] Under stirring and nitrogen protection conditions, according to the molar ratio of cellulose: sodium hydroxide: sodium 2-chloroethanesulfonate: benzyltriethylammonium chloride = 1:4:1.5:0.3, the volume ratio of alcohol to water is 9:1, 10g of cellulose is added to 200mL of isopropanol solvent, and then a sodium hydroxide solution with a mass fraction of 50% is added, and the reaction is alkalized in a 20°C water bath for 1.0h; sodium 2-chloroethanesulfonate and benzyltriethylammonium chloride are added in a formula amount, the temperature is raised to 70°C, and the reaction is maintained for 4h to obtain a reaction solution; the reaction is neutralized with a hydrochloric acid solution to a pH value of 7-8.5, and then the reactant is centrifuged to separate the organic solvent, and then it is repeatedly washed and centrifuged with an ethanol solution, and finally placed in a vacuum drying oven for drying to obtain a sulfonated cellulose product, and the number average molecular weight of the obtained product is M n 3.01×10 5 .
[0055] Example 6
[0056] Under stirring and nitrogen protection conditions, according to the molar ratio of cellulose: sodium hydroxide: sodium 2-chloroethanesulfonate: benzyltriethylammonium chloride = 1:4:2.0:0.3, the volume ratio of alcohol to water is 9:1, 10g of cellulose is added to 300mL of isopropanol solvent, and then a sodium hydroxide solution with a mass fraction of 50% is added, and the reaction is alkalized in a 40°C water bath for 2.0h; sodium 2-chloroethanesulfonate and benzyltriethylammonium chloride in a formula amount are added, the temperature is raised to 80°C, and the reaction is maintained for 7h to obtain a reaction solution; the reaction is neutralized with a hydrochloric acid solution to a pH value of 7-8.5, and then the reactant is centrifuged to separate the organic solvent, and then it is repeatedly washed and centrifuged with an ethanol solution, and finally placed in a vacuum drying oven for drying to obtain a sulfonated cellulose product, and the number average molecular weight of the obtained product is M nis 3.21×10 5 .
[0057] Comparative Example 1
[0058] Under stirring and nitrogen protection conditions, according to the molar ratio of cellulose: sodium hydroxide: chloroacetic acid = 2:2:1, the volume ratio of alcohol to water is 9:1, 10g of cellulose is added to 150mL of isopropanol solvent (), and then a 50% sodium hydroxide solution is added, and the alkalization reaction is carried out in a 20°C water bath for 1.0h; a formula amount of chloroacetic acid is added, the temperature is raised to 60°C, and the reaction is maintained for 1h to obtain a reaction solution; the acetic acid solution is neutralized to a pH value of 7-8.5, and then the reactant is centrifuged to separate the organic solvent, and then it is repeatedly washed and centrifuged with an ethanol solution, and finally placed in a vacuum drying oven for drying to obtain a carboxymethyl cellulose product, and the number average molecular weight of the obtained product is M n 3.51×10 5 .
[0059] In order to verify that the product of the invention has strong resistance to temperature and high-valent metal ions, the following drilling fluid base slurries were prepared and the drilling fluid performance was compared.
[0060] (1) Performance evaluation in freshwater drilling fluid:
[0061] Add 0.56g of anhydrous sodium carbonate and 16g of bentonite for drilling fluid preparation (according to the industry standard SY / T5490-2016, bentonite for drilling test preparation is unified as bentonite for Bohai drilling preparation) to 400mL of tap water, stir at high speed for 20min, and cure at room temperature for 24h to obtain freshwater base slurry. Add 0.5% of the sulfonated cellulose product obtained in the above Examples 1 to 6 and the carboxymethyl cellulose product obtained in Comparative Example 1 to the base slurry, stir at high speed for 20min, and obtain freshwater drilling fluid respectively. Roll and age at 150℃ for 16h, then take out, cool to room temperature, stir at high speed for 5min, and measure the drilling fluid properties respectively. The results are shown in Table 1.
[0062] (2) Performance evaluation in brine drilling fluid:
[0063] Add 16g of sodium chloride to 400mL of 4% fresh water base slurry, stir at high speed for 20min, and cure at room temperature for 24h to obtain salt water base slurry. Add 1.5% of the sulfonated cellulose product obtained in Examples 1 to 6 and the carboxymethyl cellulose product obtained in Comparative Example 1 to the base slurry, stir at high speed for 20min, and obtain salt water drilling fluids respectively. Roll and age at 150℃ for 16h, then take out, cool to room temperature, stir at high speed for 5min, and measure the drilling fluid properties respectively. The results are shown in Table 1.
[0064] (3) Performance evaluation in saturated brine drilling fluid:
[0065] Add 144g of sodium chloride to 400mL of 4% fresh water base slurry, stir at high speed for 20min, and cure at room temperature for 24h to obtain saturated brine base slurry. Add 2.0% of the sulfonated cellulose product obtained in Examples 1 to 6 and the carboxymethyl cellulose product obtained in Comparative Example 1 to the base slurry, stir at high speed for 20min, and obtain saturated brine drilling fluids respectively. Roll and age at 150℃ for 16h, then take out, cool to room temperature, stir at high speed for 5min, and measure the drilling fluid properties respectively. The results are shown in Table 1.
[0066] (4) Performance evaluation of calcium chloride in drilling fluid:
[0067] Add 12g of calcium chloride to 400mL of 4% fresh water base slurry, stir at high speed for 20min, and cure at room temperature for 24h to obtain calcium chloride base slurry. Add 2.0% of the sulfonated cellulose product obtained in the above Examples 1 to 6 and the carboxymethyl cellulose product obtained in Comparative Example 1 to the base slurry, stir at high speed for 20min, and obtain calcium chloride drilling fluids respectively. Roll and age at 150℃ for 16h, then take out, cool to room temperature, stir at high speed for 5min, and measure the drilling fluid properties respectively. The results are shown in Table 1.
[0068] Table 1 Comparison of product performance of examples and comparative examples
[0069]
[0070]
[0071] The raw material cellulose and the sulfonated fiber obtained in Example 6 were analyzed by infrared spectroscopy, and the infrared spectra thereof were as follows: Figure 3 As shown. Figure 3 It can be seen that the infrared spectrum of the sulfonated cellulose obtained in Example 6 is compared with the spectrum of the raw cellulose. -1 The -OH stretching vibration peak appeared at 1232.29 cm -1 、1178.29cm -1 The -SO3 stretching vibration peak appeared, indicating that the product molecular structure contained characteristic structures such as glucose units and sulfonic acid groups.
[0072] Meanwhile, the sulfonation degree of the sulfonated cellulose products obtained in Examples 1 to 6 was determined by elemental analysis, and the results are shown in Table 2. As can be seen from Table 2, the sulfonation degree of the sulfonated cellulose provided in the present application is in the range of 0.4 to 1.0.
[0073] Table 2 Sulfonation degree test results of sulfonated cellulose products
[0074] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Sulfonation degree 0.45 0.82 0.60 0.51 0.74 0.41
[0075] Figures 4 to 7The performance comparison chart of the sulfonated cellulose obtained in Example 5 and the carboxymethyl cellulose obtained in Comparative Example 1 in different drilling fluid base slurries is shown in FIG. Figure 4 This is a comparison chart of the fresh water slurry performance of Example 5 and the comparative example. Figure 5 This is a performance comparison chart of 4% salt water slurry of Example 5 and the comparative example. Figure 6 This is a performance comparison chart of saturated salt water slurry of Example 5 and the comparative example. Figure 7 The performance comparison diagram of Example 5 and the comparative example in 3% calcium chloride slurry is shown in Table 1 and Figures 4 to 7 It can be seen that the medium pressure filtration loss and apparent viscosity of the sulfonated cellulose obtained in Examples 1 to 6 after high temperature aging in fresh water slurry, salt water slurry, saturated salt slurry and calcium chloride slurry are significantly superior to those of the carboxymethyl cellulose in the comparative example, indicating that the sulfonic acid group in the product of the invention has good resistance to temperature, salt and calcium.
[0076] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention, but the present invention is not limited thereto. Those skilled in the art can understand that within the technical concept of the present invention, the technical solution of the present invention can be modified, or some technical features can be combined in any other way. These modifications or combinations do not make the essence of the corresponding technical solution deviate from the spirit and scope of each implementation of the technical solution of the present invention, and should be regarded as the contents disclosed by the present invention, which belong to the protection scope of the present invention.
Claims
1. A sulfonated cellulose, characterized in that: It is obtained by etherifying alkalized cellulose with water-soluble halosulfonate.
2. The sulfonated cellulose according to claim 1, characterized in that The water-soluble halogenated sulfonate is a halogenated alkyl sulfonate.
3. The sulfonated cellulose according to claim 1, characterized in that The water-soluble halosulfonate is selected from sodium 2-chloroethanesulfonate and / or sodium 2-bromoethanesulfonate.
4. The sulfonated cellulose according to claim 1, characterized in that The sulfonation degree of the sulfonated cellulose is 0.4 to 1.
0.
5. A method for preparing sulfonated cellulose, characterized in that: The following steps are involved: In a protective atmosphere, alkalized cellulose and water-soluble halosulfonate are heated under the action of a catalyst to carry out an etherification reaction to obtain sulfonated cellulose.
6. The preparation method according to claim 5, characterized in that The alkalized cellulose is prepared according to the following steps: In a protective atmosphere, cellulose is dispersed in an alcohol solvent, and a sodium hydroxide aqueous solution is added to carry out an alkalization reaction to obtain alkalized cellulose.
7. The preparation method according to claim 6, characterized in that The mass concentration of the sodium hydroxide aqueous solution is 25% to 60%; the molar ratio of the cellulose to the sodium hydroxide in the sodium hydroxide aqueous solution is 1:1 to 1:
4.
8. The preparation method according to claim 6, characterized in that The catalyst is selected from quaternary ammonium salt catalysts; the molar ratio of the catalyst to the water-soluble halosulfonate is 0.05:1 to 2:1; The molar ratio of the water-soluble halosulfonate to the cellulose is 0.5:1 to 2:
1.
9. The preparation method according to claim 6, characterized in that The temperature of the alkalization reaction is 10° C. to 40° C.; the time of the alkalization reaction is 0.5 to 2 hours; the temperature of the etherification reaction is 60° C. to 80° C.; the time of the etherification reaction is 3 to 7 hours.
10. Use of the sulfonated cellulose according to any one of claims 1 to 4 or the sulfonated cellulose prepared by the preparation method according to any one of claims 5 to 9 as a fluid loss reducer for drilling fluid.
Citation Information
Patent Citations
Sulfonated cellulose water reducer based on porous carbon sulfonic acid catalyst loaded with elemental tin, and preparation method of sulfonated cellulose water reducer
CN109279808A
High-temperature-resistant salt-resistant anti-collapse filtrate reducer for drilling fluid
CN111363524A
Preparation method of sulfonated cellulose
CN112142862A
Preparation method of modified cellulose filtrate reducer
CN115926761A
Sulfoalkyl starch, preparation method and application thereof
CN108101999A
Cited By
Easily-demoulded high-strength cast aluminum alloy material and preparation method thereof
CN121555869A
Al-Mg-Cu type motor rotor alloy material and preparation method thereof
CN121629227A
Al-Fe type motor rotor alloy material and preparation method thereof
CN121653466A
Cast aluminum alloy material with low creep deformation and good toughness and preparation method thereof
CN121737526A
Production method for producing bearing retainer by adopting pipe material
CN121798301A